2022 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2022
DOI: 10.1109/iros47612.2022.9981632
|View full text |Cite
|
Sign up to set email alerts
|

Model-free Neural Lyapunov Control for Safe Robot Navigation

Abstract: This paper presents a hierarchical reinforcement learning algorithm constrained by differentiable signal temporal logic. Previous work on logic-constrained reinforcement learning consider encoding these constraints with a reward function, constraining policy updates with a sample-based policy gradient. However, such techniques oftentimes tend to be inefficient because of the significant number of samples required to obtain accurate policy gradients. In this paper, instead of implicitly constraining policy sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Rabbit biped [43] Locomotion control Marvel biped [44] Navigation control 8-DoF quadruped [45] Walking on 2D stepping stones AMBER-3M biped [46] Walking on 3D stepping stones ANYmal quadruped [47] Navigation control Digit biped [48] Locomotion control AMBER2 7-DoF biped [49] Navigation control 21-DoF biped [50] Locomotion control DURUS 23-DoF biped [51] Walking on 2D stepping stones Rabbit biped [52] Locomotion control Compass-gait walked biped [53] Locomotion control AMBER-3M [65] Navigation Control Laikago [36] Locomotion control Compass-gait walked biped…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rabbit biped [43] Locomotion control Marvel biped [44] Navigation control 8-DoF quadruped [45] Walking on 2D stepping stones AMBER-3M biped [46] Walking on 3D stepping stones ANYmal quadruped [47] Navigation control Digit biped [48] Locomotion control AMBER2 7-DoF biped [49] Navigation control 21-DoF biped [50] Locomotion control DURUS 23-DoF biped [51] Walking on 2D stepping stones Rabbit biped [52] Locomotion control Compass-gait walked biped [53] Locomotion control AMBER-3M [65] Navigation Control Laikago [36] Locomotion control Compass-gait walked biped…”
Section: Applicationsmentioning
confidence: 99%
“…The problem of exponentially stabilizing periodic orbits in a special class of hybrid models was addressed in [43] using CLF. The proposed solution based on a variant of CLF that enforces rapid exponential convergence to the zero dynamics [44] to navigate towards a target location, in an environment filled with obstacles. (b) CBF with episodic learning on AMBER-3M biped controlled to walk on stepping stones, the time evolution of the barrier function at episode 0 [45] is reported in the panel where the distance between the robot feet and the stone centres is depicted.…”
Section: Lf/clf Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the importance of safety in path planning, the lack of a clear metric to quantify this factor has been noted [7], [40], [47]- [50]. Some studies have reported a qualitative evaluation on safety, such as the absence of collisions [51]. However, considering localization error, information delay and other factors, the passing through the edge of obstacles (though not collided) is also extremely dangerous.…”
Section: Path Safetymentioning
confidence: 99%